Application of Self-Compassion to Communication and Conflict Resolution in the Property Management Industry - Erin A. Hopkins (Journal of Real Estate Practice and Education)
As conflict is inevitable in the property management industry, communication and conflict resolution are essential skills for students to possess in order to have a successful career trajectory. However, existing research shows that students struggle with these soft skills thereby creating a gap between expected soft skills and observed soft skills of recent graduates. The purpose of this paper is to share details of a self‑compassion intervention that is used in a property management operations course and provide student insights into the exercise to illuminate self‑compassion as a concept that can be used to aid in communication and conflict resolution within the property management industry.